أثر استخدام طريقة لعب الأدوار في تنمية التفكير التأملي لدى تلامذة الصف الخامس الأساسي في مادة التاريخ - صالح, وئام (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aimed to identify the impact of the use of method of playing roles in the teaching of historical concepts on the development of reflective thinking among a sample of students in the fifth grade in the city of Damascus composed of (100) students were randomly assigned to two groups officer and pilot in each group (50) student. The study identified a problem in the answer to the following question: What effect the use of role-playing games in the way of teaching historical concepts on the development of reflective thinking among students in the fifth grade in the city of Damascus?To answer the questions of the study has been applied method of playing roles in teaching historical concepts on the development of reflective thinking, as the researcher has built a test reflective thinking and which consisted of (34) items distributed on the five skills (observation and meditation, developing solutions proposed interpretation, conclusion, detect fallacies).The results showed statistically significant differences in favor of the experimental group in all dimensions of the test reflective thinking and total score at Mrtfie and low achievement in the experimental group and the study recommended way to take advantage of playing roles in the development of historical concepts.هدفت الدراسة إلى التعرف على أثر استخدام طريقة لعب الأدوار في تنمية التفكير التأملي لدى عينة من تلامذة الصف الخامس الأساسي في مادة التايخ في مدينة دمشق مكونة من (100 ) طالبا وطالبة وزعت عشوائيا على مجموعتين ضابطة وتجريبية في كل مجموعة (50) طالبا وطالبة. حددت مشكلة الدراسة في الإجابة على السؤال الرئيس التالي :ما أثر استخدام طريقة لعب الأدوار في تنمية التفكير التأملي لدى تلامذة الصف الخامس الأساسي في مادة التاريخ ؟وللإجابة على أسئلة الدراسة تم تطبيق طريقة لعب الأدوار في تدريس مادة التاريخ في تنمية التفكير التأملي ، كما قامت الباحثة ببناء اختبار التفكير التأملي و الذي تكون من (34) فقرة موزعة على خمس مهارات (الملاحظة والتأمل , وضع حلول مقترحة ، التفسير ، الاستنتاج ، الكشف عن المغالطات ) أظهرت النتائج وجود فروق ذات دلالة إحصائية لصالح المجموعة التجريبية في جميع أبعاد اختبار التفكير التأملي والدرجة الكلية لدى مرتفعي ومتدني التحصيل في المجموعة التجريبية وأوصت الدراسة بالاستفادة من طريقة لعب الأدوار في تنمية المفاهيم التاريخية و تدريس مادة االتاريخ .